Incidence and factors associated with the recurrence of Rathke's cleft cyst after surgery: A systematic review and meta-analysis - Qian, Ao; Zhou, Jing; Zhang, Xin; Yu, Jiaojiao; Wang, Xiaoshu (Frontiers in Surgery, 2023)
Backgroud Recurrence of Rathke's cleft cyst (RCC) is not uncommon after surgery, and the associated factors and incidence of relapse deserve a systematic summary. Methods This study was conducted in accordance with Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. The Pubmed, Embase, Cochrane, and Web of Science databases were searched until September 12, 2022. Studies with significant results of recurrent factors or specific incidences of RCC recurrence and mean/median follow-up time were included. Based on a protocol of a 2-year interval grouping, included studies were categorized into four groups with follow-up periods <24 months, 24–48 months, 48–72 months, and ≥72 months, respectively. Quality assessment was performed using the NOS score. Pooled estimations were computed by using a random-effects model in the STATA “metaprop” command. Publication bias was assessed visually through a funnel plot and statistically through Egger's linear regression test and Begg's correlation test. Results A total of 44 studies were included containing 2,539 cases. Squamous metaplasia was the most commonly reported factor, followed by the extent of cyst removal. The other factors were reported individually. The pooled overall incidences of RCC recurrence after surgery in four groups of the follow-up period were 7.4% (95%CI = 4.1–11.3%) in <24 months, 13.1% (95%CI = 9.7–17.0%) in 24–48 months, 13.7% (95%CI = 7.7–21.0%) in 48–72 months, and 33.8% (95%CI = 19.6–49.6%) in ≥72 months. The pooled symptomatic incidences were 2.3% (95%CI = 0.4–5.1%) in <24 months, 5.6% (95%CI = 3.6–7.9%) in 24–48 months, 5.9% (95%CI = 2.4–10.6%) in 48–72 months, and 14.1% (95%CI = 6.0–24.5%) in ≥72 months. A dramatic increase in recurrent incidence was observed when the follow-up period was more than 72 months in both overall and symptomatic recurrence. A similar trend of recurrence was found in subgroup analyses stratified by publication year, cohort size, and cyst resection strategy. Conclusion This study systematically reviewed recurrent factors and described the profile of trends in RCC recurrent incidence after surgery with a follow-up time based on a protocol of a 2-year interval, finding a dramatic increase in recurrent rates with a follow-up period of more than 72 months. This encouraged us to put forward a recommendation of at least a 6-year follow-up after surgery for patients with RCC. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42021278970.